CRISPR-based molecule-regulatory expression platform for specific immunotherapy of cancer - Tong, Lu; Wang, Linlin; Dong, Jun (Frontiers in Oncology, 2024)
IntroductionCancer is still a major challenge of human health. The abnormality of intracellular cancer-related signal pathways is an important mechanism for the occurrence of cancer.MethodsWe used a molecular-senor to act on the endogenous signal molecules within the cell to redirect the abnormal signal flows in the cell to treat cancer. Based on CRISPR-dCas12f procedures, we combined aptamers and ribozymes to construct riboswitches, which served as molecular switches to reprogram sgRNAs, so that CRISPR-dCas12f redirected the intracellular anti-cancer signal flows after sensing specific input signal molecules. In addition, the activated molecular sensors and the inhibitory molecular sensors were constructed by combining transcription factors (VP64) and transcription inhibitors (KRAB) to specifically activate and inhibit target genes of interest.ResultsOur experimental results showed that the molecular sensors that we designed and constructed specifically sensed the endogenous signal molecules and then redirect the cancer related signal networks of cancer cells. In addition, corresponding logic gates were constructed to distinguish cancer cells from normal cells and redirect anticancer signal flows to trigger specific cancer immunotherapy.ConclusionThe constructed molecular sensors constructed specifically recognized the signal molecules within the cell and redirected the endogenous signal pathway to reprogram the fate of cancer cells.